Low-temperature thermal degradation of disinfected COVID-19 non-woven polypropylene-based isolation gown wastes into carbonaceous char - Harrussani, M. M; Rashid, Umer; Sapuan, S. M.; Abdan, Khalina (MDPI AG, 2021)
Yields of carbonaceous char with a high surface area were enhanced by decreasing the temperature to improve the conversion of hazardous plastic polypropylene (PP), the major component in abundantly used isolation gowns. This study applied pyrolysis with different low pyrolytic temperatures to convert disinfected PP-based isolation gown waste (PP-IG) into an optimised amount of char yields. A batch reactor with a horizontal furnace was used to mediate the thermal decomposition of PP-IG. Enhanced surface area and porosity value of PP-IG derived char were obtained via an optimised slow pyrolysis approach. The results showed that the amount of yielded char was inversely proportional to the temperature. This process relied heavily on the process parameters, especially pyrolytic temperature. Additionally, as the heating rate decreased, as well as longer isothermal residence time, the char yields were increased. Optimised temperature for maximum char yields was recorded. The enhanced SBET values for the char and its pore volume were collected, ~24 m2 g−1 and ~0.08 cm3 g−1, respectively. The char obtained at higher temperatures display higher volatilisation and carbonisation. These findings are beneficial for the utilisation of this pyrolysis model in plastic waste management and conversion of PP-IG waste into char for further activated carbon and fuel briquettes applications, with the enhanced char yields, amidst the COVID-19 pandemic.